DETERMINANTS OF AZERBAIJAN’S NON-ALIGNMENT POLICY - Kumar, Vinod (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper explains the determinants of Azerbaijan’s foreign policy, particularly its non-alignment policy. Azerbaijan became a member of the Non-Aligned Movement in 2011. Immediately after joining this organization, Azerbaijan considered this principle a natural extension of its long-standing "balanced foreign policy" of multi-directional engagement, rather than a change in its foreign policy. After the formal declaration of the Non-Aligned Movement in 1961, all emerging nations adopted the policy of non-alignment as their foreign policy principle. The concept of non-alignment aims to allow developing countries to pursue an independent foreign policy, free from the constraints of Cold War power blocs and their associated pressures. For Azerbaijan, the Non-Aligned Movement provides a platform to diversify its foreign relations beyond the world’s major powers, institutionalize its balanced policy, and engage with the Global South. Therefore, Azerbaijan’s non-alignment is the result of a pragmatic foreign policy based on international realities.